The Evangelical Perspective on Unity and the Contribution of the Protestant Evangelical Council to Christian Fellowship in Croatia - Mladen Jovanović (Kairos (English Ed.), 2008)
Unity is not just an unfulfilled idea of the Christian world. It is the axiom of reliability and sustainability of the Church founded in the Bible. Throughout history the Church has demonstrated that without unity it ceases to be “salt and light.” Unity cannot be imposed as an ideology, but can only be built through fellowship. This is the witness of the churches of the Reformation tradition in Croatia which have proved in the last twenty years that many great things occur when God’s children come together.